2010
DOI: 10.1128/aem.00185-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Host Cells on Low- and Medium-Pressure UV Inactivation of Adenoviruses

Abstract: UV disinfection is highly effective against most pathogens, with the exception of the adenoviruses (AD).UV disinfection has increasingly been adopted as a favorable technology for disinfection worldwide. It does not involve any disinfection by-product (DBP) formation and is highly effective against protozoan, bacterial, and most viral pathogens at low doses (40 to 60 mJ/cm 2 ) commonly rendered in water treatment plants. Despite numerous advantages over other disinfectants, a major concern pertaining to low-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…The fluence was higher than other studies reporting 64 mJ/cm 2 (Nwachuku et al, 2005) for 2 log inactivation of AdV5. However, a study of Guo et al (2010) showed a wide range of fluence required for 2 log inactivation, which was 26 to 76 mJ/cm 2 . The result of the study clearly explained that difference of host cells using for infectivity assay affected log inactivation of AdV5.…”
Section: Results and Discussion Microbial Inactivation By Uv Or Chlorinementioning
confidence: 99%
“…The fluence was higher than other studies reporting 64 mJ/cm 2 (Nwachuku et al, 2005) for 2 log inactivation of AdV5. However, a study of Guo et al (2010) showed a wide range of fluence required for 2 log inactivation, which was 26 to 76 mJ/cm 2 . The result of the study clearly explained that difference of host cells using for infectivity assay affected log inactivation of AdV5.…”
Section: Results and Discussion Microbial Inactivation By Uv Or Chlorinementioning
confidence: 99%
“…This is likely because damage to DNA caused by LP UV lamps can be repaired but the more widespread damage inflicted by MP or pulsed UV cannot; such damage can be expected to prevent host cell reactivation of adenovirus as well. Indeed, recent work has shown that greater inactivation of adenovirus in cell culture is achieved by both MP and pulsed UV than by LP UV (Eischeid et al, 2009;Guo et al, 2010;Linden et al, 2007); over 4-log inactivation of adenovirus can be achieved using approximately 40 mJ/cm 2 of MP or pulsed UV, and this is in much closer agreement with the LP UV doses required to inactivate other viruses.…”
Section: Ultraviolet Disinfection Technologiesmentioning
confidence: 55%
“…Furthermore, formation of pyrimidine dimers in adenoviral DNA after irradiation appears to be similar to that found in mammalian cells and bacteria (Eischeid et al, 2009;Rainbow and Mak, 1973), and reports from the medical literature in which UV-irradiated adenoviruses are assayed for infectivity in DNA repair-deficient host cells clearly indicate that adenovirus is sensitive to LP UV in these cells (Day, 1974;Rainbow, 1980;Rainbow, 1989). More recently, Guo et al (2010) have shown that adenoviruses are more susceptible to both LP and MP UV in repair-deficient cells. This effect is especially pronounced after LP UV treatment, when DNA repair is expected to make the greatest difference.…”
Section: Uv Disinfection Of Adenovirus Previous Work On Uv Treatment mentioning
confidence: 87%
“…A lower required fluence of 80 mJ/cm 2 for 2 log inactivation was reported by Baxter et al (2007). This difference could be attributed to many factors, such as the use of different cell lines for the plaque assay (Guo et al 2010) or a difference in the water matrix used for the UV exposure experiments. For the Cl 2 -deCl 2 -UV process, the purpose of adding the dechlorinating agent, sodium thiosulfate, was to investigate the effect of pretreatment by chlorine before UV exposure.…”
Section: Uv and CL 2 -Decl 2 -Uvmentioning
confidence: 81%